To Investigate the Morphological Characteristics of Lung Fissures and Trachea - Md. Hassan Ali (Asian Journal of Medical Research, 2017)
Background: The study of tracheal length and lung architecture has been infrequent, although it has been shown that the structure of the lung exhibits substantial variation. Furthermore, there are only a limited number of surgeries performed on the trachea, resulting in a lack of substantial knowledge among surgeons in this area. The aim is to investigate the Morphological Characteristics of Lung Fissures and Trachea. Methodology: This research is an observational investigation that analyzes data on tracheal length, body length, sex, and the physical architecture of the lungs in 50 cadavers. A study was conducted to examine the association between tracheal length and body length, as well as tracheal length and sex. Additionally, the study investigated morphological changes in lung structure. The lungs were categorized based on their side, either right or left, and the structure of the fissures was documented, including the number, extent, and completeness, using the Craig-Walker classification. Results: The mean tracheal length, measured from the inferior margin of the cricoid cartilage to the subcarinal region, was 9.88±1.98 cm, while the mean height of the individual was 147.32±12.54 cm. The research sample consisted of 35 male and 15 female cadavers. The average tracheal length for men was 10.34±1.78, and the average height was 151.11±11.46. The mean tracheal length for females was 9.06±1.74, whereas the mean height was 138.12±8.94. A direct relationship was seen between the length of the trachea and the height of the body. The Pearson's coefficient was 0.76 with a p value of 0.001. Conclusion: The lungs possess diverse anatomical features, and a comprehensive understanding of their morphology, including the extent of fissure incompleteness, can aid in comprehending the development of conditions such as pneumonia and pleural effusion, as well as the dissemination of diseases acquired via the lungs.